Investigating Sensory Play Implementation with Loose Parts Media In Early Childhood Education - Patimah, R. Titim; Nurhayati, Sri (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research aims to investigate the implementation of sensory play with loose parts as a pedagogical approach in early childhood education, with a focus on a case study conducted at Daycare Baiturrahmah, Kota Bandung. The study employed a qualitative case study approach involving three educators and five toddlers as research participants. Data collection methods included observations, document study, and semi-structured interviews. Findings emerged regarding the factors supporting effective implementation, such as material selection and collaborative teacher efforts. Challenges were identified, including emotional management and combatting boredom, suggesting the need for ongoing adaptation and innovative strategies. The study also highlighted the positive feedback from parents, indicating high levels of child engagement and satisfaction. The research findings resonate with existing literature, underlining the value of sensory play in early childhood education. Implications for practice emphasize the significance of embracing sensory play as a pedagogical strategy. Future research directions include exploring long-term effects, innovative strategies for challenges, and enhanced parental involvement.